Auditoría Financiera a la Estación de Servicios “Cooperativa de Transportes Patria”, del Cantón Riobamba, período 2022. - Toalombo Saltos, Erika Denisse (2025)
This research work, entitled “Financial Audit of the Service Station 'Cooperativa de Transportes Patria,' Riobamba Canton, 2022 Period,” aims to assess the reasonableness of the service station's financial statements through a financial audit based on the International Standards on Auditing (ISA). These standards facilitated the evaluation of the reliability and accuracy of the most significant accounts, such as Property, Plant, and Equipment, and Various Accounts Payable, due to their high materiality and relevance to the financial statements. The methodology employed follows a qualitative approach with a documentary and field design and a descriptive research level. This approach enabled an in-depth understanding of the company's accounting and financial processes through the review of key documentation and on-site observation. It allowed for the evaluation of compliance with current accounting and tax regulations, as well as the effectiveness of internal controls applied during the audited period. The results reveal deficiencies in the formalization of policies for fixed asset management and the lack of segregation of duties in key areas, which may impact the reliability of the presented financial information. Based on these findings, recommendations are proposed to enhance the transparency and reliability of the financial statements, ensuring their reasonableness for users of financial information.